Improving the measurement efficiency of marine ship-borne receivers of global navigation satellite systems - Hlynianiuk, Vasyl; Konovets, Viktor; Kuzmenko, Vitalii; Pleshko, Eduard; Rudenskyi, Roman; Shyshkin, Oleksandr (Technology audit and production reserves, 2025)
Global navigation satellite systems (GNSS) play a decisive role in maritime navigation. The differential mode of operation of ship-based GNSS receivers using coordinate corrections allows to significantly increase the accuracy of positioning of a seagoing vessel compared to the autonomous mode. The object of the study was marine GNSS receivers capable of operating in differential mode. This research examines the problems of reliably determining the actual operating mode of a shipboard GNSS receiver (autonomous or differential). It outlines the risks associated with the ambiguity and unreliability of standard differential mode indicators (flags posMode = D, Fix Quality = 2). This leads to misinterpretation of the accuracy status by related navigation systems, in particular, the Automatic Identification System (AIS), and poses a threat to maritime safety. It has been experimentally proven that outdated receiver models can falsely indicate operation in differential mode, relying solely on user settings rather than the actual receipt and application of corrections. It has been established that modern receivers solve this problem but create a new level of complexity by separating the concepts of “accuracy” and “integrity” of the navigation solution. They can produce a highly accurate position while simultaneously flagging it as unreliable (NavStatus flag = V) if a faulty satellite is detected. A systemic conflict between the requirements of the International Telecommunication Union (ITU) and International Electrotechnical Commission (IEC) standards regarding high-accuracy criteria for AIS has been identified. It has been established that inaccurate mode indications in outdated equipment are related to the particularities of its software logic, which links the mode flag to the setting rather than to the availability of data. The behavior of modern receivers is explained by the implementation of advanced integrity control algorithms (RAIM) and the logic of new standards (in particular, IEC 61108-7), which require reporting the loss of confidence in data. The research results can be used by developers of marine equipment (AIS, ECDIS) to create comprehensive GNSS data analysis algorithms that take into account a set of indicators. International organizations (IMO, ITU) can use them to harmonize standards. Ship operators and technical specialists can use these results to form a correct understanding of the limitations of standard indicators and the need for a comprehensive assessment of the status of the GNSS receiver.